2022
DOI: 10.1039/d2gc02972c
|View full text |Cite
|
Sign up to set email alerts
|

Bromine radical-enhanced HAT activity leading to stoichiometric couplings of methylarenes with acid chlorides

Abstract: The stoichiometric coupling of readily available methylarenes and diverse acid chlorides into α-aryl ketones, a valued structure motif present in pharmacological relevance molecules, has been developed. The utility of this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…24 g , h Additionally, we have proved the feasibility of using the bromine radical as an efficient hydrogen atom transfer (HAT) reagent for accelerating the generation of a stable benzyl radical. 18,25 By rational reaction design, we envisioned that in the presence of a bromine radical, methylarenes undergo HAT to deliver benzyl radical. To validate our hypothesis, we initiated our study by evaluating the visible-light catalyzed pyridylation reaction of 1-methoxy-4-methylbenzene 2a with 4-cyanopyridine 1a as model substrates in the presence of Ir(dF(CF 3 )ppy) 2 (dtbpy)PF 6 ( PC1 ), LiBr, acetone and H 2 O as a co-solvent under the irradiation of 35 W blue light at room temperature for 16 h (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 g , h Additionally, we have proved the feasibility of using the bromine radical as an efficient hydrogen atom transfer (HAT) reagent for accelerating the generation of a stable benzyl radical. 18,25 By rational reaction design, we envisioned that in the presence of a bromine radical, methylarenes undergo HAT to deliver benzyl radical. To validate our hypothesis, we initiated our study by evaluating the visible-light catalyzed pyridylation reaction of 1-methoxy-4-methylbenzene 2a with 4-cyanopyridine 1a as model substrates in the presence of Ir(dF(CF 3 )ppy) 2 (dtbpy)PF 6 ( PC1 ), LiBr, acetone and H 2 O as a co-solvent under the irradiation of 35 W blue light at room temperature for 16 h (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding other photocatalysts, including 4CzIPN ( PC2 ), Ru(bpy) 3 Cl 2 ( PC3 ), fac -Ir(ppy) 3 ( PC4 ), Rose Bengal ( PC5 ), and Eosin Y ( PC6 ), only PC2 afforded products (Table 1, entries 5–6). Among the tested photocatalysts, PC1 with an excited state that exhibits sufficient oxidizing ability ( E 1/2 (PC*/PC˙ − ) = +1.21 V vs. SCE) 25 was demonstrated to be the optimal photocatalyst. We studied the effect of other bromide HAT reagents and found that NaBr, NH 4 Br, and TBAB offered moderate efficiency (Table 1, entry 7), while CH 2 Br 2 and NiBr 2 exhibited low reactivity (Table 1, entry 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was inhibited to a large extent in toluene and CH 2 Cl 2 and shut down completely in CH 3 CN and DMF (entries 7 and 8, respectiely). The investigation of HAT catalysts rendered ethyl 2-mercaptoacetate (13) the most effective one, although triisopropylsilanethiol (14) furnished comparable results (entries 9 and 10). Other thiol-based HAT catalysts such as tert-dodecylmercaptan (15), 3-(trimethoxysilyl)propanethiol (16), and p-toluenethiol (17) were all ineffective (entries 11−13, respectively).…”
mentioning
confidence: 99%
“…Employing acyl fluorides as the acylation reagent, Studer and co-workers realized a benzylic C–H acylation via NHC and photoredox dual catalysis (Scheme A, bottom) . In addition, the NHC-catalyzed cross-coupling of benzylic C–H bonds with aldehydic C–H bonds was also established by Li and Zeng et al Generally, these reactions proceed through either a trapping of an iminium ion with a Breslow intermediate or a radical–radical coupling of an NHC-bound ketyl radical with a benzylic radical. , Through cooperative photoredox and nickel catalysis, Doyle, Shibasaki, Hong, Rueping, Deng, and Huo unveiled the acylation of α-nitro C(sp 3 )–H bonds, α-oxy C(sp 3 )–H bonds, aliphatic C(sp 3 )–H bonds, and benzylic C–H bonds using carboxylic acid derivatives such as acyl halides and anhydrides as the acylation reagents (Scheme B). Mechanistically, an alkyl acyl Ni(III) species was proposed as the key intermediate responsible for these acylation reactions.…”
mentioning
confidence: 99%